Developing Computer-assisted Hotel Front Office English Listening Materials for Students of Tourism School in Bali - Astini, K.T. (Universitas Pendidikan Ganesha, 2018)
This study aimed at exploring materials that should be developed in computer-assisted hotel front office English listening materials for students of tourism school, explaining ways to develop computer-assisted hotel front office English listening materials for students of tourism school in Bali, and analyzing the quality of computer-assisted hotel front office English listening materials for student of tourism school in Bali. This study applied ADDIE model Research and Development design. The steps were analyzing, designing, developing, implementing, and evaluating. From the need analysis, it was found that listening activity was one of the skills that got the least attention. Therefore, developing listening material in the context of front office was an urgent need. In the development, several data were collected through observation, interview, and document analysis. There were five topics developed based on the collected data, they were Hotel Check-in, Hotel Check-in with No Reservation, Giving Recommendation, Hotel Check-out, and Hotel Check-out with Problem. The resource materials followed good material criteria proposed by Tomlinson (1998) and good listening text criteria by Wilson (2008). Using the quality measurement, the developed resource material was 169.3 (good).